Mind the Divide Surrounding Knowledge Representation - Bibel, Wolfgang (Advances in Knowledge Representation, Logic Programming, and Abstract Argumentation, 2015)
The paper identifies the so-called belief sets mediation problem as one of those important issues which tend to fall into the cracks between KR and its neighboring areas and thus do not receive the deserved attention by KR. It also questions the exclusive restriction of KR on the traditional linguistic (or symbolic) representation of knowledge and argues for a widening of the research agenda in this respect in collaboration with neighboring fields. These specific issues are embedded in a general view of knowledge and its representation.